2023
DOI: 10.3390/molecules28031058
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Characterization and Bactericidal Action of Lysozyme, Isolated from Bacillus subtillis BSN314: A Disintegrating Effect of Lysozyme on Gram-Positive and Gram-Negative Bacteria

Abstract: In the present study, lysozyme was purified by the following multi-step methodology: salt (ammonium sulfate) precipitation, dialysis, and ultrafiltration. The lysozyme potential was measured by enzymatic activity after each purification step. However, after ultrafiltration, the resulting material was considered extra purified. It was concentrated in an ultrafiltration centrifuge tube, and the resulting protein/lysozyme was used to determine its bactericidal potential against five bacterial strains, including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…The previous research showed the high abundance of Bacilli in some stations of mangroves could be signatures of human interferences often cause infections in humans [73] . Virulence genes identified from the Sundarbans resistance to antibiotics confirmed by high abundance of ARGs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous research showed the high abundance of Bacilli in some stations of mangroves could be signatures of human interferences often cause infections in humans [73] . Virulence genes identified from the Sundarbans resistance to antibiotics confirmed by high abundance of ARGs.…”
Section: Discussionmentioning
confidence: 99%
“…DNA extraction in conventional way and kit based techniques [ 39 , 73 ] was used to obtain the DNA from the isolated 11 specimens (FS2, FS3, FS4, SS1, SS3, SS4, SS5, WS1, WS3, WS4 and WS5) from the different samples of the Sundarban following the manufacturer's instruction. The PureLink Microbiome DNA Purification Kit minimized the need to order individual kits for specific sample types because it has been optimized for use with a wide range of biological samples.…”
Section: Methodsmentioning
confidence: 99%
“…Bacillus subtilis exhibits enormous potential as a suitable host for biochemical production, primarily due to its excellent growth characteristics and adept bioresource utilization 16 . It is often employed as a host carrier for the production of industrially important enzymes such as lysozyme, cellulase, and amylase as well as for the synthesis of specific substances, including selenium nanoparticles, and other essential compounds 17 , 18 . Accordingly, this study shows a keen interest in cellulase-producing Bacillus subtilis strains and further aims to obtain the target strain through systematic screening experiments and optimization of the cultivation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Their cell envelope consists of the cytoplasmic membrane holding the cell contents; the peptidoglycan layer, which consists of lipoproteins, phospholipids, porin proteins, lipopolysaccharide, and other proteins; and an external outer membrane that provides mechanical strength ( Weckesser et al, 1995 ; Rojas et al, 2018 ). This enables gram-negative bacteria to withstand lysozyme cell lysis better than gram-positive bacteria ( Naveed et al, 2023 ). Moreover, photosynthetic bacteria like PNSB have an additional intracytoplasmic membrane (ICM) adjoined to the inner membrane to facilitate energy harvest from light, potentially increasing the cells’ resistance to cellular disruption ( Oikonomou and Jensen, 2021 ).…”
Section: Introductionmentioning
confidence: 99%